Controversial Advert Perceptions in SNS Advertising: The Role of Ethical Judgement and Religious Commitment - Kadić-Maglajlić, Selma (Journal of business ethics, 2017)
This study attempts to advance knowledge in the area of controversial advertising by examining the antecedents and consequences of controversial advert perceptions in the context of social media, and particularly social networking sites (SNS). Specifically, we explore how ethical judgement and religious commitment shape controversial advert perceptions leading to attitudes towards the advert, brand attitudes and purchase intentions. Our results indicate that when a SNS advert is judged to be ethically acceptable, the level of perceived advert controversy is lower. However, the impact of ethical judgement on controversial advert perceptions becomes significant and positive when intrapersonal commitment and interpersonal religious commitment are introduced as moderators. This result implies that the level of religious commitment changes the ethical judgement–controversial advert perceptions relationship. The results also highlight that controversial advert perceptions negatively influence attitude towards the advert. The study contributes to the limited knowledge on controversial advertising on SNS, yielding significant and relevant implications for academics and advertisers alike, in their effort to improve advertising effectiveness without offending or alienating target audiences.